PENGARUH HEALTH EDUCATION PADA LANSIA PENDERITA HIPERTENSI TERKAIT POLA HIDUP SEHAT - Amelli, Destia; Latifah, Laily Nurul; Khotimah, Neng Nurul; Meidian, Risha; Wardiani, Zahraisyya; Ridwan, Heri (Universitas Pahlawan Tuanku Tambusai, 2025)
Hypertension is one of the most common health problems experienced by the elderly, with variousimpacts affecting their quality of life. The nursing process through the provision of health education isa major strategy to raise awareness of the elderly regarding lifestyle for more effective hypertensionmanagement by involving planning and implementation. This study aims to evaluate the effect ofhealth education on healthy lifestyle changes in the elderly with hypertension. The library reviewmethod used is scoping reviews from various scientific databases such as Google Scholar, Pubmed,and Crossref. From 1,390 journals that were initially discovered and analyzed based on abstracts,research objectives, full text reading, and criteria from 2015- 2024, up to 7 relevant journals wereobtained. Research results show that health education plays an important role in increasing theelderly's understanding of the importance of balanced diet, regular physical activity, and medicalcompliance. Therefore, this study emphasizes the importance of structured and sustainable healtheducation in improving the quality of life for the elderly with hypertension